1977
DOI: 10.4039/ent1091335-10
|View full text |Cite
|
Sign up to set email alerts
|

A SEX PHEROMONE MIXTURE FOR THE BERTHA ARMYWORM MOTH, MAMESTRA CONFIGURATA: (Z)-9-TETRADECEN-1-OL ACETATE AND (Z)-11-HEXADECEN-1-OL ACETATE

Abstract: An abdominal tip extract of female bertha armyworm moths, Mamestra configurata (Walker), was found to contain two sex pheromone components. One corresponded to (Z)-11-hexadecen-1-ol acetate, previously identified from this source, and the other to a tetradecen-1-ol acetate, identified by gas chromatography – mass spectrometry. Data obtained from the EAG profile of isomeric tetradecen-1-ol acetates indicated the active component to be (Z)-9-tetradecen-1-ol acetate. Neither of these two acetates was by itself at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The combination of (Z)‐9‐14:AC and (Z)‐11‐16:AC attracted numbers of both M. configurata and P. saucia , although attracting no male S. praefica . Underhill et al . (1977) reported these two chemicals as the sex attractant pheromone of M. configurata and Byers & Struble (1987) trapped M. configurata with mixtures including (Z)‐9‐14:AC and (Z)‐11‐16:AC.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of (Z)‐9‐14:AC and (Z)‐11‐16:AC attracted numbers of both M. configurata and P. saucia , although attracting no male S. praefica . Underhill et al . (1977) reported these two chemicals as the sex attractant pheromone of M. configurata and Byers & Struble (1987) trapped M. configurata with mixtures including (Z)‐9‐14:AC and (Z)‐11‐16:AC.…”
Section: Discussionmentioning
confidence: 99%
“…This potent attractant inhibitor (Underhill et al 1977) also inhibited the attraction of A. cogitata. The addition of 12:Ac, 14:Ac, 16:Ac, Z7-16:Ac, Z9-16:Ac and 29-14:OH at 5kg singly or in various combinations with the reference blend had no effect (P < 0.05) on the attraction of males.…”
mentioning
confidence: 88%
“…Electroantennogram responses of male antennae to synthetic isomeric tetradecenyl acetates and attractancy tests under field conditions showed that the highest number of males were captured with a blend of Z9-14:Ac : Z11-16:Ac in a ratio of 1:19 (Underhill et al 1977). This blend has been useful for monitoring the relative abundances of bertha armyworm; however, in 162 monitor traps in southern Alberta from 1979 to 1982, the catches consisted of 18.4% Agroperina cogitata (Sm) .…”
mentioning
confidence: 99%
“…Therefore, a more specific, less labourious means of monitoring populations of adult M. configurata was needed. Discovery of species-specific pheromones emitted by females to attract males (Chisholm et al 1975;Struble et al 1975) and the synthetic production of these compounds (Underhill et al 1977) provided the opportunity to develop a highly effective monitoring system for M. configurata. A research team consisting of personnel from the National Research Council, Agriculture Canada, Saskatchewan Agriculture, and Alberta Agriculture developed a pheromone trapping system for M. configurata (Steck et al 1979(Steck et al , 1984.…”
Section: Population Monitoringmentioning
confidence: 99%